Quantifying Islamic Precautions: A Statistical Exploration of Pandemic Strategies - Dr. Muhammad Samiullah; Sami Ullah Khan Niazi (AL-IDRAK JOURNAL, 2024)
The research focuses on district Mianwali's vaccination staff, students, parents, teachers, and AIOU affiliates, totaling 500 respondents selected through simple random sampling. Gender sensitivity is maintained, with a 3-point Likert scale questionnaire featuring 65 questions across three sections. A pilot study ensures the questionnaire's reliability, involving vaccinators, doctors, parents, teachers, and others. Validity is confirmed through pilot testing, and reliability is established post-pilot. Data collection includes personal visits, telephonic contacts, and distribution of both hard and soft copy questionnaires. Findings highlight widespread ignorance among respondents regarding Quranic injunctions, guidance in Sirat-e-Tayyaba, and prophetic hadiths related to pandemic prevention. The study exposes misconceptions about concepts such as lockdown, vaccination, quarantine, and social distancing within Islamic tutelage. The chaotic atmosphere during the pandemic, economic downturns, and fear-driven actions are also explored. The conclusion underscores the need for comprehensive awareness campaigns to bridge the gap between Islamic teachings and public understanding. Recommendations propose continuous policy revision, national-level research, and government-led initiatives for awareness, training, and education. Integration of Islamic teachings into the educational curriculum and collaboration with media for disseminating information are suggested measures. The study advocates for embracing Islamic guidance as a comprehensive approach to pandemic management, emphasizing the need for a collective societal shift toward a more informed and prepared future.